Effect of submicron deformations on the transmission of all-solid photonic bandgap fibre - Konyukhov, Andrey I.; Romanova, Elena A.; Benson, Trevor M.; Athanasiou, Giorgos S.; Lousteau, Joris; Scarpignato, Gerardo; Pugliese, Diego; Milanese, Daniel (Springer, 2016)
Waveguide losses in all-solid photonic bandgap fibre are studied numerically using both vectorial mode solver and vectorial beam propagation methods. Confinement loss, including material losses, is comprehensively evaluated for defect modes of hexagonal lattice photonic bandgap fibre. The excitation of the index-guiding modes at the bandgap edges leads to a narrowing of the transmission bands. Submicron deformations of the transverse structure of the fibre lead to a significant reduction in the width of the transmission bands, yet the minimum value of the losses within these bandgaps remains practically unchanged. Longitudinal variation of the fibre profile increases the effective losses by up to tens of dB/m.